2003
DOI: 10.3998/ark.5550190.0004.606
|View full text |Cite
|
Sign up to set email alerts
|

On the mechanism of α-phenylation of β-keto esters with diaryl-λ3-iodanes: evidence for a non-radical pathway

Abstract: Reaction of [(o-allyloxy)phenyl](phenyl)-λ 3 -iodane with the potassium enolate of 2-(methoxycarbonyl)-1-indanone in t-BuOH at room temperature afforded a mixture of α-phenylation and α-(o-allyloxy)phenylation products in 61 and 7% yields, with no evidence for the formation of 3-substituted dihydrobenzofuran derivatives. A mechanism involving the intermediacy of aryl radicals in the α-arylation of β-keto ester enolates with diaryl-λ 3 -iodanes is not compatible with the intramolecular aryl radical trapping exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 3 publications
1
22
0
Order By: Relevance
“… 9 This selectivity can be overruled by steric bulk in the ortho position, thus leading to the selective transfer of that aryl group, irrespective of electronic properties (the so-called ortho effect). 6a c However, there are several examples of ortho -substituted aryl groups with various electronic properties that have not been transferred, 3b , 6d e thus making predictions and the design of unsymmetrical salts difficult.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… 9 This selectivity can be overruled by steric bulk in the ortho position, thus leading to the selective transfer of that aryl group, irrespective of electronic properties (the so-called ortho effect). 6a c However, there are several examples of ortho -substituted aryl groups with various electronic properties that have not been transferred, 3b , 6d e thus making predictions and the design of unsymmetrical salts difficult.…”
Section: Resultsmentioning
confidence: 99%
“…Chemoselectivities that are due to electronic differences have been explained by a polarized ligand-coupling transition state, in which the developing charges are better stabilized by the substituents when the more electron-deficient group is transferred. 6d e A recent computational study found a correlation between the chemoselectivity and the natural charge differences on the ipso -carbon atom of the aryl ligand in the hypervalent bond. 6h On the other hand, the ortho effect has been rationalized by the bulkiest aryl group occupying the equatorial position in the T-shaped intermediate, because this position is less crowded than the apical position.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The addition of an aryl radical trap to the reaction did not affect the outcome, which indicates that radical pathways are unlikely and the reaction occurs by direct coupling of the ligands on the hypervalent iodine center. 49 It has been found that in the reaction of unsymmetric diaryliodonium salts 16 with nucleophiles, the most electron-deficient aryl group is transferred to the nucleophile with varying selectivities in agreement with the mechanism outlined in Scheme 8. The initial ligand exchange affords the hypervalent intermediates 17 and 18, in which with the electronegative ligand Nu occupies an axial position in agreement with general principles of hypervalent bonding.…”
Section: Mechanism Of Nucleophilic Substitution Reactions Of Iodoniummentioning
confidence: 52%
“…We hence designed a novel diaryliodonium reagent, carrying both a leaving group and a strong EWG in addition to the highly electron-withdrawing iodonium moiety, to evaluate the strategy (Figure 1c). We speculated that the unusual structure of the iodonium reagent might enable initial SNAr over the usual ligand coupling (LC) pathway, 11,33 and deliver a unique iodine(III) intermediate that could undergo a subsequent aryl transfer to yield a diarylated product with the iodine substituent retained.…”
mentioning
confidence: 99%